2014
DOI: 10.1111/bjd.13276
|View full text |Cite
|
Sign up to set email alerts
|

Most individuals with either segmental or non-segmental vitiligo display evidence of bilateral cochlear dysfunction

Abstract: Bilateral cochlear dysfunction is common in both NSV and SV and does not reflect the appearance of vitiligo in the skin. Our results underscore the important role of melanocytes and melanin in cochlear function, and suggest that the cochlear abnormalities in SV point to the presence of additional nonsegmental pathophysiological events underlying all forms of vitiligo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 13 publications
(34 reference statements)
1
24
0
1
Order By: Relevance
“…This difference was not statistically significant, and the authors concluded that, contrary to observations in early onset vitiligo, late onset vitiligo did not seem to be associated with audiological abnormalities . Another study comparing the cochlear function of patients with NSV and SV demonstrated that bilateral cochlear dysfunction was common in both subtypes of the disease . A study by Gopal et al .…”
Section: Ocular and Audiological Abnormalities In Patients With Vitiligomentioning
confidence: 87%
See 2 more Smart Citations
“…This difference was not statistically significant, and the authors concluded that, contrary to observations in early onset vitiligo, late onset vitiligo did not seem to be associated with audiological abnormalities . Another study comparing the cochlear function of patients with NSV and SV demonstrated that bilateral cochlear dysfunction was common in both subtypes of the disease . A study by Gopal et al .…”
Section: Ocular and Audiological Abnormalities In Patients With Vitiligomentioning
confidence: 87%
“…The association between vitiligo and audiological abnormalities are highlighted in the literature . Melanocytes are also distributed in the membranous labyrinth of the inner ear with the heaviest pigmentation in scala vestibuli.…”
Section: Ocular and Audiological Abnormalities In Patients With Vitiligomentioning
confidence: 99%
See 1 more Smart Citation
“…Progressive skin depigmentation in vitiligo is associated with the loss of melanocytes from the basal layer of the epidermis . Other organs can be affected, and patients sometimes incur visual or auditory impairment . Loss of hair pigmentation can follow depigmentation of the skin and rarely precedes it …”
Section: Introductionmentioning
confidence: 99%
“…3 The aetiopathogenesis of NSV and SV has not been fully elucidated, and it is possible that the two subtypes share common mechanisms for initiation of the disease, but diverge in the progression phase, as depigmentation rapidly stabilizes in SV, but not NSV. 5 There is much data to support an autoimmune phase in the extension of vitiligo, and mechanical and chemical trauma are known environmental stressors that accelerate disease appearance. However, the events that initiate the loss of melanocytes are still a subject of debate.…”
mentioning
confidence: 99%